Observational Study Of Demographic And Management Protocols Of Intestinal Obstruction In Tertiary Care Centres Of Urban Population (Indian Journal of Applied-Basic Medical Sciences, 2020)
INTRODUCTION: Intestinal obstruction is frequently encountered in differential diagnosis of patients  presenting with a acute abdomen. Even with an early diagnosis bowel obstruction still  represent some of the most difficult problems that surgeons face with regard to optimal  timing of therapy and appropriate management in different type of bowel obstruction. AIMS AND OBJECTIVES: To study the various modes of presentation, importance of early diagnosis and  management of patients , the incidence of different complications during treatment and  their management in tertiary care centre of urban population. MATERIALS AND METHODS: This study was conducted for a period of 2 years with patients admitted from 01/ 07/ 2017  up to 30/06/ 2019 with a sample size of 50 patients in L.G. hospital, Ahmedabad .Present  study was prospective, observational, cross-sectional study.  OBSERVATIONS AND DISCUSSION: Out of 50 patients, 70% were males and 30% were females, more commonly in young  patients (11-20 yrs age). Most common presenting cause of intestinal obstruction is  subacute intestinal obstruction which is 20 % and these cases were managed conservatively.  Conservative approach was helpful in 38% of cases due to their early presentation and subacute type of obstruction most commonly. Primarily operative approach after initial  resuscitation were 32% of total cases with indications like acute presentation with  tenderness, abnormal peristalsis like absent or hyperperistalsis, fever, irreducible or  palpable lump, ultrasonography finding of peritonitis etc. Most common complication  encountered was wound infection 35% of operated cases. Mortality was 4 % occurrence in  present study.  CONCLUSION: Of the 50 cases of intestinal obstruction in our study adhesions and bands are  the common cause to produce intestinal obstruction. Koch’s abdomen is also increasingly  encountered in etiology of intestinal obstruction as stricture and it is related to poor  socioeconomic status of study population in present study. Hernia related obstruction were  higher in early twentieth century but decreasing nowadays. It suggests that planned hernia  repair can avoid this complication. With better understanding of etiology due to advanced  diagnostic ailments mortality rate is decreasing.
Keywords: Intestinal Obstruction; Management; Koch’s abdomen; mortality; stricture; Complications; infection